2017
DOI: 10.1007/s00213-017-4653-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the serotonin 2C receptor agonist WAY163909 on the abuse-related effects and mesolimbic dopamine neurochemistry induced by abused stimulants in rhesus monkeys

Abstract: Rationale Accumulating evidence shows that the serotonergic system plays a major role in psychostimulant abuse through its interactions with the dopaminergic system. Studies indicate that serotonin 5-HT2C receptors are one of the main classes of receptors involved in mediating the influence of serotonin in drug abuse. Objective The aim of the present study was to evaluate the effects of the selective serotonin 5-HT2C receptor agonist WAY163909 on the behavioral neuropharmacology of cocaine and methamphetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…The 5-HT 2C R agonist Ro 60-0175 reduced cocaine intake in squirrel monkeys [19], and lorcaserin reduced nicotine [25] and alcohol [26] intake in rats. In a previous study, the same doses of WAY163909 used here reduced drug intake and drug seeking of METH and cocaine [21] in rhesus monkeys. One study reported that 7-day treatment with lorcaserin, which is less selective for the 5-HT 2C R and exhibits more 5-HT 2A R agonist activity than WAY163909 [40], did not attenuate cocaine vs food choice [48].…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The 5-HT 2C R agonist Ro 60-0175 reduced cocaine intake in squirrel monkeys [19], and lorcaserin reduced nicotine [25] and alcohol [26] intake in rats. In a previous study, the same doses of WAY163909 used here reduced drug intake and drug seeking of METH and cocaine [21] in rhesus monkeys. One study reported that 7-day treatment with lorcaserin, which is less selective for the 5-HT 2C R and exhibits more 5-HT 2A R agonist activity than WAY163909 [40], did not attenuate cocaine vs food choice [48].…”
Section: Discussionmentioning
confidence: 61%
“…One study reported that 7-day treatment with lorcaserin, which is less selective for the 5-HT 2C R and exhibits more 5-HT 2A R agonist activity than WAY163909 [40], did not attenuate cocaine vs food choice [48]. This study evaluated only male rhesus monkeys; whereas, the study using WAY163909 [21] used males and females. Moreover, the drug self-administration paradigms and actual compounds used were different, which may also account for the opposing results.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations